Use of nanobarcodes particles in bioassays - Freeman, R Griffith; Raju, Paul A; Norton, Scott M; Walton, Ian D; Smith, Patrick C; He, Lin; Natan, Michael J; Sha, Michael Y; Penn, Sharron G (Methods in molecular biology (Clifton, N.J.), 2005)
We have developed striped metal nanoparticles, Nanobarcodes particles, which can act as encoded substrates in multiplexed assays. These particles are metallic, encodeable, machine-readable, durable, submicron-sized tags. The power of this technology is that the particles are intrinsically encoded by virtue of the difference in reflectivity of adjacent metal stripes. This chapter describes protocols for the attachment of biological molecules, and the subsequent use of the Nanobarcodes particles in bioassays.